Book review Aborcja w polskich sporach społeczno-prawnych lat 1919-1997 (Abortion in Polish socio-legal disputes in 1919-1997) by Miła Kwapiszewska, Łukasz Moniuszko, Jacek Raniszewski, Kraków: Wydawnictwo Avalon - Stria, Maciej (Studia Ecologiae et Bioethicae, 2019)
The summary is not available.